Whatever works: Dualisation and the service economy in Bismarckian welfare states - Werner Eichhorst; Paul Marx (Institute for the Study of Labor (IZA), 2010)
The paper compares employment structures in five Continental welfare states. These countries feature broad similarities in their reliance on a more dualised model of labour market flexibility, particularly in service occupations with low skill requirements. However, a closer look also reveals considerable differences between national patterns of standard and non-standard work. In Germany (and to a lesser extent Austria), marginal part-time provides a fertile ground for low-paid service jobs, as non-wage labour costs are minimised. In France, fixed-term contracts are a flexible and also cheaper alternative to permanent contracts, especially for younger workers. Dutch service sector employers follow an eclectic approach, as can be seen from high shares of self-employed and part-timers, as well as temporary workers. Finally, Belgium has large proportions of very low-skilled, own-account self-employed and involuntary fixed-term contracts. On the basis of these results, we identify four transformative pathways towards a more inclusive or flexible labour market: growing wage dispersion, defection from both permanent full-time employment as well as from dependent employment, and government-sponsored labour cost reductions.
Keywords: J38; J41; J21; J58; 330; Labour market dualisation; Continental Europe; fixed-term contracts; part-time work; wage dispersion; Arbeitsverhältnis; Dualer Arbeitsmarkt; Arbeitsmarktflexibilisierung; Sozialstaat; Dienstleistungssektor; Lohnstruktur; Ungeschützte Beschäftigung; Lohnsubvention; Vergleich; Deutschland; Frankreich; Niederlande; Belgien; Österreich